Percutaneous Management of Urinary Calculi in Horseshoe Kidneys - Soufi Majidpour, Heshmatollah; Yousefinejad, Vahid (Urology Journal, 2008)
Urolithiasis in horseshoe kidney presents a unique challenge in decision-making and technical aspects of calculus treatment. We present our experience with a group of patients with symptomatic calculi in their horseshoe kidneys. We had 8 patients with 9 horseshoe kidneys bearing calculi. They all underwent percutaneous nephrolithotomy. The median size of the calculi was 21 mm (range, 12 to 45 mm). Auxiliary therapeutic procedures were required in 2 patients who had residual calculi on control imaging. The stone-free status was observed in 6 patients (75.0%) at discharge, and in 7 (87.5%) after 3 months of follow-up. Surgical complications included bleeding in 2 patients that was controlled with complete bed rest and blood transfusion, and pleural injury in 1 which was managed conservatively.